Satisfaction evaluation of interns with Da Vinci robot surgical demonstration training in gynecologic oncology operations - Junfen Xu; Junfen Xu; Yumei Zhou; Mengyan Tu (Frontiers in Public Health)
ObjectiveThis study aimed to assess the satisfaction levels of medical interns undergoing training in Da Vinci robot-assisted surgery at the Women’s Hospital.DesignBetween Aug 2023 and Mar 2024, an intern surgical demonstration training was conducted with students in medicine in the Department of Gynecologic Oncology. While the doctor operated from the primary console, a student utilized the 3D perspective from the second console to closely follow the lead surgeon’s surgical maneuvers in real-time. After completing the training, the students filled out a questionnaire to assess their satisfaction with the proposed training.ResultsThrough structured questionnaires and interviews, 18 interns’ perceptions and suggestions regarding the training program were evaluated. All students supported the Da Vinci surgical teaching model over traditional teaching methods. The findings revealed the interns’ overall satisfaction with an average five-point Likert scale score of 4.88. Students’ responses highly evaluated the usefulness of Da Vinci surgical training in improving surgical practice capabilities with an average five-point Likert scale score of 4.78. 94% of the students looked forward to using the da Vinci surgical system in future surgeries, and 83% of the participants would continue their further education and training in the field of robotic surgery. Using a 10-point scoring system to evaluate students’ mastery of surgical knowledge gained from this training, the average score obtained was 8.94. Notably, follow-up data revealed that 12 out of these 18 students eventually chose surgery as their specialization when selecting their master’s degree direction.ConclusionTraining in robot-assisted surgery demonstration of gynecologic oncology operations is a useful approach for training students to master surgical anatomy and develop skills in the field of surgery.